Working bodies : chronic illness in the Canadian workplace - Stone, Sharon Dale, 1955-; Crooks, Valorie A., 1976-; Owen, Michelle K. (McGill-Queen's University Press, 2014)
While significant research has been produced in the field of disability studies, little attention has been paid to experiences of chronic illness. This book emphasizes the workplace as an important site for understanding such experiences, as employment status has an enormous impact on social and economic standing in Canadian society.